REPEATED TAX AMNESTY DECONSTRUCTION IN FULFILLING JUSTICE ACCORDING TO ACCOUNTING - Situmorang, Bornok; Sawarjuwono, Tjiptohadi (Widya Mandala Surabaya Catholic University, 2023)
Research Purposes. This study aims to explain the process of deconstructing justice in the recurring tax amnesty policy as economic events that are recorded and reported using accounting so that justice according to accounting is accommodated in it.Research MethodsThis study uses a qualitative approach in which the researcher adopts a poststructuralist paradigm, especially Derrida's deconstruction.Research Results and Findings. The practice of deconstructing justice can be seen clearly in discussions on the legal plan at the government level, debates on the legal draft, ratification of laws, judicial review, adoption of accounting standards for assets, attempts by taxpayers to file objections and post-implementation monitoring goals recurring tax amnesty. The accountant also accommodates all of these deconstruction processes and is involved in them, thereby strengthening the concept of justice according to accounting. This study provides a theoretical and practical description of the deconstruction process of universal justice and justice according to accounting in the recurrent tax amnesty policy.